Hermite-Hadamard Type Fractional Integral Inequalities for Generalized (r;s,m,varphi)-preinvex Functions (European Journal of Pure and Applied Mathematics, 2017)
In the present paper, a new class of generalized $(r;s,m,φ)$-preinvex functions is introduced and some new integral inequalities for the left hand side of Gauss-Jacobi type quadrature formula involving generalized $(r;s,m,φ)$-preinvex functions are given. Moreover, some generalizations of Hermite-Hadamard type inequalities for generalized $(r;s,m,φ)$-preinvex functions via Riemann-Liouville fractional integrals are established. These results not only extend the results appeared in the literature (see \cite{AkRl}, \cite{AkYil}), but also provide new estimates on these types.